The novel chimeric multi-agonist peptide (GEP44) reduces energy intake and body weight in male and female diet-induced obese mice in a glucagon-like peptide-1 receptor-dependent manner - Blevins, James E.; Honeycutt, Mackenzie K.; Slattery, Jared D.; Goldberg, Matvey; Rambousek, June R.; Tsui, Edison; Dodson, Andrew D.; Shelton, Kyra A.; Salemeh, Therese S.; Elfers, Clinton T.; Chichura, Kylie S.; Ashlaw, Emily F.; et al. (Frontiers in Endocrinology, 2024)
We recently reported that a novel chimeric peptide (GEP44) targeting both the glucagon-like peptide-1 receptor (GLP-1R) and neuropeptide Y1-and Y2 receptor (Y1R and Y2R) reduced energy intake and body weight (BW) in diet-induced obese (DIO) rats. We hypothesized that GEP44 reduces energy intake and BW primarily through a GLP-1R dependent mechanism. To test this hypothesis, GLP-1R +/+ mice and GLP-1R null (GLP-1R -/-) mice were fed a high fat diet for 4 months to elicit diet-induced obesity prior to undergoing a sequential 3-day vehicle period, 3-day drug treatment (5, 10, 20 or 50 nmol/kg; GEP44 vs the selective GLP-1R agonist, exendin-4) and a 3-day washout.Energy intake, BW, core temperature and activity were measured daily. GEP44 (10, 20 and 50 nmol/kg) reduced BW after 3-day treatment in DIO male GLP-1R +/+ mice by -1.5±0.6, -1.3±0.4 and -1.9±0.4 grams, respectively (P<0.05), with similar effects being observed in female GLP-1R +/+ mice. These effects were absent in male and female DIO GLP-1R -/-mice suggesting that GLP-1R signaling contributes to GEP44-elicited reduction of BW. Further, GEP44 decreased energy intake in both male and female DIO GLP-1R +/+ mice, but GEP44 appeared to produce more consistent effects across multiple doses in males. In GLP-1R -/-mice, the effects of GEP44 on energy intake were only observed in males and not females, suggesting that GEP44 may reduce energy intake, in part, through a GLP-1R independent mechanism in males. In addition, GEP44 reduced core temperature and activity in both male and female GLP-1R +/+ mice suggesting that it may also reduce energy expenditure. Lastly, we show that GEP44 reduced fasting blood glucose in DIO male and female mice through GLP-1R. Together, these findings support the hypothesis that the chimeric peptide, GEP44, reduces energy intake, BW, core temperature, and glucose levels in male and female DIO mice primarily through a GLP-1R dependent mechanism.